Amino acid imbalance in cystinuria. Issue 6 (June 1974) - Asatoor, A. M.; Freedman, P. S.; Gabriel, J. R. T.; Milne, M. D.; Prosser, D. I.; Roberts, J. T.; Willoughby, C. P.
Abstract : After oral ingestion of a free amino acid mixture by three cystinuric patients, plasma increments of lysine and arginine were lower and those of many other amino acids were significantly higher than those found in control subjects. Similar results were obtained in control subjects after amino acid imbalance had been artificially induced by the omission of cystine, lysine, and arginine from the amino acid mixture. Especially high increments of alanine and proline provided the best evidence of amino acid imbalance caused by a temporary lysine and, to a lesser extent, arginine and cystine deficit. No such amino acid imbalance was found to occur in the cystinuric patients after ingestion of whole protein, indicating that absorption of oligopeptides produced by protein digestion provided a balanced physiological serum amino acid increment. This is considered to explain the lack of any unequivocal nutritional deficit in cystinuric patients despite poor absorption of the essential free amino acid, lysine.